Runway capacity and congestion delays at Gatwick Airport august 1985 (Civil Aviation Authority LondonGB, 1987)
Reports on a study which took place at Gatwick in August 1985. Recommends that due to the increasing proportion of departure flow regulated (DFR) traffic and the need to achieve slot times, the application of different Air Traffic Control (ATC) procedures to cope with these situations requires further investigation and study.
DC